KOMPETENSI KEPALA SEKOLAH, SARANA DAN PRASARANA BERPENGARUH TERHADAP KINERJA GURU - Efriadi, Joni; Rahyasih, Yayah; Rosita, Tita (Universitas Muhammadiyah Surakarta, 2023)
The level of teachers’ performance in executing their primary duties at school is significantly influenced by the competence of the school principal and the completeness of school facilities. This research aims to statistically measure the impact of school principals' competence and school facility completeness on the performance of vocational school teachers in the Anabas Islands Regency. To achieve this objective, a quantitative research design with a correlative approach was employed. The study population comprised 55 teachers serving in three vocational schools in the Anabas Islands Regency. The research instrument was validated using the Pearson Product Moment, and data reliability was verified through the Cronbach Alpha test. The results of the study revealed that (1) principal competence is linked to teacher performance, and that principal competence has a minimal impact on the performance of vocational school teachers. (2) Facilities and infrastructure were found to be associated with the performance of vocational teachers. The facilities and infrastructure significantly influenced the performance of vocational teachers. (3) The competence of the school principal, facilities, and infrastructure exert a significant influence on the performance of vocational schoolteachers. The competence of the school principal, facilities, and infrastructure also had a minimal impact on the performance of vocational school teachers.